ANALISIS KEMAMPUAN KOGNITIF SISWA KELAS VIII SMP NEGERI 11 JEMBER DITINJAU DARI GAYA BELAJAR DALAM MENYELESAIKAN SOAL POKOK BAHASAN LINGKARAN - Vidayanti, Nurul; Sugiarti, Titik; Kurniati, Dian (Kadikma, 2017)
Abstract: This research aims to analyze cognitive ability of eight graders in Junior High School 11 Jember viewed from the learning style in solving problems of circle subject. This research is descriptive research with qualitative approach. Data collection method which were used are questionnaire, test and interview. Research subject is students of VIII A Junior High School 11 Jember which consists of 35 students. Cognitive ability that is observed is cognitive ability based on Bloom’s taxonomy which consists of six levels that are remember, understand, apply, analyze, evaluate, and create. The research’s result showed that cognitive ability which is possessed by students with visual learning style tend to be able to reach the level of evaluating especially in evaluating relations between two circle. Cognitive ability which is possessed by students with auditorial learning style tend to be able to reach the level of remember especially in recalling circle's elements and recalling formula of circles' circumference and area. Cognitive ability which is possessed by students with cinestetic learning style tend to be able to reach the level of apply especially in aplicating circle's element in a picture. Keywords:Cognitive Ability, Learning Style, Circle Subject.